FAKTOR AUDIT DELAY PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR PADA BURSA EFEK INDONESIA. - sopi - sopi; Zumrotun Nafiah (JURNAL CAPITAL : Kebijakan Ekonomi, Manajemen dan Akuntansi, 2022)
Timeliness of audit report adjustment is one of the auditor's professional criteria. The longer the audit delay, the longer the auditor will complete his audit work. The purpose of the effectiveness of this study is to determine the effect of company size, profitability and audit opinion on audit delay in food and beverage companies listed on the Indonesia Stock Exchange for the 2019-2021 period. The sampling technique used purposive sampling method, as many as 9 companies for three years to 27 samples and using multiple linear regression data analysis method. From this research, it can be concluded that hypothesis testing with T test results that firm size and audit opinion have no effect on audit delay, while profitability has an effect on audit delay. Many studies on audit delays in food and beverage companies have shown mixed results. For further researchers should also be able to develop a research model, the research period with the addition of other research variables.